Handbook of research on updating and innovating health professions education post-pandemic perspectives - Ford, Channing R.; Garza, Kimberly, 1975- (Advances in medical education, research, and ethics (AMERE) book series., 2022)
"This book explores the impact a global pandemic has made on health professions education, specifically lessons learned and best practices and highlights the adoption and implementation of technology as a result of COVID-19 that have produced innovative and exciting changes in the way we prepare our learners for practice"--